1974
DOI: 10.1080/10862967409547101
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Scanning and Syntactic Processing Three Reading Experiments — First and Second Language Learners

Abstract: To test the acoustic scanning hypothesis for reading, three experiments were conducted with monolingual and bilingual subjects. Ss performed a crossout task, cancelling letters in a text as they read it for comprehension. Letters remaining uncancelled were then analyzed. In Experiment 1, letters were frequently unmarked in function words, words which are highly predictable since they serve primarily to mark case relationships between content words. Changing passage difficulty did not effect the ratio of letter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
23
0

Year Published

1982
1982
1994
1994

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 4 publications
2
23
0
Order By: Relevance
“…Although one could infer that the possibility of different processing of nouns and of verbs is another reflection of the impact of linguistic characteristics on word recognition, more research is needed to substantiate this suggestion. With respect to word class, English readers tended to process content words to a greater extent than they did function words, in agreement with the findings in previous studies (Hatch et al, 1974;Healy, 1976;Schindler, 1978;Taylor & Taylor, 1983).…”
Section: The Effect Of Linguistic Characteristics On the Reading Processsupporting
confidence: 82%
“…Although one could infer that the possibility of different processing of nouns and of verbs is another reflection of the impact of linguistic characteristics on word recognition, more research is needed to substantiate this suggestion. With respect to word class, English readers tended to process content words to a greater extent than they did function words, in agreement with the findings in previous studies (Hatch et al, 1974;Healy, 1976;Schindler, 1978;Taylor & Taylor, 1983).…”
Section: The Effect Of Linguistic Characteristics On the Reading Processsupporting
confidence: 82%
“…It may be that subjects took longer to fmd and judge pronounced letters because there were more phonemes to scan in these words. Corcoran (1966Corcoran ( , 1967 and Hatch et al (1974) have proposed acoustic scanning as a process operating when spellings are inspected for letters. Some evidence for acoustic scanning was uncovered in Experiment 4, in which plausible-sounding absent letters were found to take longer to reject than implausible letters.…”
Section: Resultsmentioning
confidence: 99%
“…He found that in both tasks, silent Es were missed more often than pronounced Es. Venezky (cited in Hatch, Polin, & Part, 1974) attempted to replicate the cross-out task with the letters H, D, and A, as well as E, but did not find a silent-pronounced difference. Instead, he found that letters in function words (e.g., articles, prepositions, and conjunctions) were more frequently left unmarked than were letters in content words (e.g., nouns, adjectives, and verbs).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some evidence suggests that such slowed second-language reading may arise, in part, from a reduced sensitivity to orthographic, syntactic, and semantic redundancies of the language (Favreau et al, 1980;Hatch, Polin, & Part, 1974), which increases the reader's dependency on the purely visual information (Massaro, 1975). Slower secondlanguage reading has also been associated with differences in the fixation time of eye movements.…”
mentioning
confidence: 99%